Production of non-biodegradable compounds based on biomass activity in a submerged ultrafiltration hollow fibre membrane biorector treating raw whey - Hasar, H; Kinaci, C; Ünlü, A (Elsevier Sci Ltd, 2004)
Raw whey including a high organic load in the range of 16-60 kg/m(3) per day was treated directly in a submerged membrane bioreactor (sMBR). The behavior of non-biodegradable compounds in the system and their effects on biomass viability were investigated by considering different sludge ages in the range of 10-75 days during an operation of 114 days. Non-biodegradable compounds were produced by dead and old organisms and then accumulated in the system. Furthermore, biomass viability decreased with an increase in sludge age. At sludge ages of 10 and 20 days, inert COD, which is a measure of non-biodegradable compounds, was removed together with the wasted sludge as a small amount of the system, but not taken away from the bioreactor at higher sludge ages due to the small amount of the wasted sludge. The production of non-biodegradable compounds was very clear at high sludge ages in the range of 30-75 days. Inert COD increased to 1.84 times at the fifth period when the sludge age was 75 days, based on the reduction of biomass viability. The ratio of mixed liquor volatile suspended solid to mixed liquor suspended solid (MLVSS/MLSS) decreased with time although both concentrations increased. The relationship between specific oxygen uptake rate (sOUR) and MLVSS was a logarithmic decreasing curve. The relationship between the sOUR and the C-s/C-0 means that the ratio of inert COD concentration in the effluent to that in the influent was an exponent decreasing curve. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: submerged membrane bioreactor; whey treatment; non-biodegradable compounds; biomass viability